The language laboratory and the EFL course / El laboratorio de idiomas y la clase de inglés como lengua extranjera - Navas Brenes, César Alberto (Universidad de Costa Rica, 2006)
This article examines the role of the audio-language laboratory in language teaching. The writer explains that the language laboratory is still a very helpful tool because learners can reinforce certain areas in which they are experiencing some difficulty such as the internalization of correct grammatical structures, pronunciation, and listening comprehension. This article contains a brief analysis of the results of a survey questionnaire that was given to students of the Conversational English Courses belonging to the Extension Program at the University of Costa Rica. Based on these results, the writer explains that the language laboratory is an essential component in this type of EFL program. El presente artículo examina la eficacia del laboratorio de idiomas en la enseñanza del inglés. El autor explica que el laboratorio de idiomas es una herramienta de gran utilidad con el objetivo de reforzar áreas en las cuales los alumnos presentan alguna dificultad tales como la gramática, la pronunciación inglesa y la comprensión auditiva. El artículo contiene un breve análisis de los resultados de un cuestionario dado a los alumnos de los Cursos de Conversación Inglesa perteneciente al Programa de Extensión Docente de la Universidad de Costa Rica. El autor explica que dicha herramienta es un componente esencial en este tipo de programas de inglés como lengua extranjera.